2023
DOI: 10.2174/1567205020666230525154300
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological Attributes of Fenugreek with Special Reference to Alzheimer’s Disease

Abstract: Background: An annual plant, Fenugreek (Trigonellafoenum-graecum L.) has well-known health care benefits in Ayurvedic and Chinese medicine. Its leaves and seeds have alkaloids, amino acids, caumarins, flavonoids, saponins, and other bioactive components. Various pharmacological properties such as antioxidants, hypoglycemic, and hypolipidemic have been attributed to fenugreek. Trigonelline, diosgenin, and 4- hydroxyisoleucine have shown neuroprotection against Alzheimer’s disease, and the extract have also been… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…Currently, it is widely planted in Asia, Africa, and Mediterranean countries. India is the main producer of fenugreek [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Currently, it is widely planted in Asia, Africa, and Mediterranean countries. India is the main producer of fenugreek [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…These metabolites may have pharmacological effects on human diseases. It has been found that trigonelline, diosgenin, and 4-hydroxyisoleucine have neuroprotective effects on Alzheimer’s disease [ 3 ]. These compounds have antibacterial, anti-inflammatory, anticancer, antiviral, antioxidant, hypoglycemic, etc., activities [ 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%